Ancient DNA suggests dwarf and 'giant' emu are conspecific. - Tim H Heupink (Public Library of Science (PLoS), 2011)
Background The King Island Emu (Dromaius ater) of Australia is one of several extinct emu taxa whose taxonomic relationship to the modern Emu (D. novaehollandiae) is unclear. King Island Emu were mainly distinguished by their much smaller size and a reported darker colour compared to modern Emu. Methodology and results We investigated the evolutionary relationships between the King Island and modern Emu by the recovery of both nuclear and mitochondrial DNA sequences from sub-fossil remains. The complete mitochondrial control (1,094 bp) and cytochrome c oxidase subunit I (COI) region (1,544 bp), as well as a region of the melanocortin 1 receptor gene (57 bp) were sequenced using a multiplex PCR approach. The results show that haplotypes for King Island Emu fall within the diversity of modern Emu. Conclusions These data show the close relationship of these emu when compared to other congeneric bird species and indicate that the King Island and modern Emu share a recent common ancestor. King Island emu possibly underwent insular dwarfism as a result of phenotypic plasticity. The close relationship between the King Island and the modern Emu suggests it is most appropriate that the former should be considered a subspecies of the latter. Although both taxa show a close genetic relationship they differ drastically in size. This study also suggests that rates of morphological and neutral molecular evolution are decoupled.